Development Of A Social Skills Training Model For Experiential Learning-Based Package A Learning Residents In South Surabaya - Durrotun Nafisa; Fakhruddin Fakhruddin; Mintarsih Arbarini (JURNAL MANAJEMEN PENDIDIKAN, 2026)
Students in Package An equality education at the Community Learning Activity Center (PKBM) generally have more limited opportunities for social interaction than students in formal schools, so the development of social skills is an important need in the learning process. This research aims to develop an experiential learning-based social skills training model for Package A learning residents in South Surabaya and test the feasibility of the developed model. The research uses the Research and Development (R&D) method which refers to the simplification of the Borg and Gall models by Sukmadinata, including three stages, namely preliminary study, model development, and validation test. The training model is designed through role play activities, group discussions, and games that provide a hands-on learning experience. The results of the study show that the training model developed is able to improve the social skills of learning residents in interacting in the learning environment. In addition, the results of validation by expert judgement showed that the experiential learning-based training model was declared feasible to be applied in learning in the Package A equality education program at PKBM. Thus, the training model developed can be an alternative learning that supports the development of social skills of citizens to learn effectively through meaningful learning experiences.